Phytoremediation of Arsenic in Mine Wastes by Acacia mangium - Rosli, Ruhan Asyrani; Shamsul Harumain, Zakuan Azizi; Zulkalam, Mohd Faizuddin; Abdul Hamid, Azzmer Azzar; Sharif, Mohd. Faez; Mohamad, Mohd Azrul Naim; Noh, Abdul Latif; Shahari, Rozilawati (Wiley, 2021)
This study explored the potential of Acacia mangium to remediate arsenic present in mine wastes and to determine the remediation mechanism of this plant for removing arsenic. A preliminary test using soil spiked with various arsenic concentrations showed that Acacia mangium was able to survive on arsenic‐contaminated soil with concentrations up to 500 mg kg−1 arsenic. Ex situ phytoremediation studies using mine wastes containing approximately 790 mg kg−1 arsenic also showed no toxicity effect on Acacia mangium throughout 5 months of treatment. Bioconcentration and translocation factors indicate that Acacia mangium utilizes phytostabilization as its main mechanism to uptake arsenic into the plant tissues. The use of the chemical lixiviants monoammonium phosphate and citric acid was also found to increase the translocation of arsenic from roots to stems of Acacia mangium with a 12‐ and sixfold increase, respectively, compared with the un‐dosed plants. Further speciation analysis revealed that arsenic in the form of arsenate was the only arsenic species detected in the stems after being amended with monoammonium phosphate; thereby, suggesting a sensible strategy for more efficient targeted arsenic phytoremediation by Acacia mangium.